2017
DOI: 10.1136/jnnp-2016-315325
|View full text |Cite
|
Sign up to set email alerts
|

Impulsivity in Parkinson’s disease is associated with altered subthalamic but not globus pallidus internus activity

Abstract: These findings provide further evidence of STN involvement in impulsive behaviour in the PD population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 16 publications
(16 reference statements)
1
9
0
Order By: Relevance
“…This role of the STN is consistent with the involvement of the corticobasal ganglia circuits in proactive and reactive inhibition of movement and cognition 8,9 . Markers of impulse control disorders were found in the STN of PD patients during rest 10 and risk decision tasks 11,12 . However, a full understanding of the underlying activity at the single neuron level is still missing.…”
supporting
confidence: 67%
See 1 more Smart Citation
“…This role of the STN is consistent with the involvement of the corticobasal ganglia circuits in proactive and reactive inhibition of movement and cognition 8,9 . Markers of impulse control disorders were found in the STN of PD patients during rest 10 and risk decision tasks 11,12 . However, a full understanding of the underlying activity at the single neuron level is still missing.…”
supporting
confidence: 67%
“…8,9 Markers of impulse control disorders were found in the STN of PD patients during rest 10 and risk decision tasks. 11,12 However, a full understanding of the underlying activity at the single neuron level is still missing. Here, we investigate the possibility of identifying subjects displaying ICB with microelectrode recordings (MERs) 13 performed at rest for target identification during DBS implant surgery.…”
mentioning
confidence: 99%
“…Several limitations in our study have to be addressed. The use of fictive monetary rewards may be considered a limitation, although it has been successfully used in previous similar experiments . Neuroimaging studies revealed that real and fictive rewards recruit overlapping neural networks, suggesting that our results could be reasonably extrapolated to a situation involving a real reward.…”
Section: Discussionmentioning
confidence: 82%
“…Few studies have examined the electrophysiology of PD patients with ICDs. PD patients with ICDs have proportionally more reward-responsive neurons and less loss-responsive neurons in the STN (159). In a stop signal task with a small sample of 10 PD patients, STN high frequency (35–75 Hz) oscillatory activity decreased during inhibition (160).…”
Section: Neural Substratementioning
confidence: 99%